6. EVALUATION OF THE OUTCOMES OF CARERING FOR PATIENT AFTER GASTRECTOMY AT THE ABDOMINAL SURGERY DEPARTMENT 2, K HOSPITAL, IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the outcomes of caring for patients after gastrectomy.Materials and Research Methods: A cross-sectional descriptive study was conducted on 57 gastric cancer patients receiving postoperative care at the Abdominal Surgery Department 2, K Hospital. Data were collected based on observations of the care process and the clinical condition of the patients in the department, using a standardized medical record for all study subjects.Results: The average hospital stay for patients in the study was 8.5±1.98 days for total gastrectomy and 7.91±2.01 days for subtotal gastrectomy. Early postoperative bleeding complications were recorded in 2 out of 57 patients, accounting for 3.5%. Care activities, including monitoring vital signs, dressing changes for surgical wounds, gastric tubes, abdominal drainage, and urinary catheters, were closely followed according to regulations. Postoperative pain was well-controlled, with no patients experiencing severe or very severe pain after surgery. At the time of discharge, 56.1% of patients reported no pain, 40.3% had mild pain, and 3.6% had moderate pain. Health education was provided to 100% of the patients.Conclusion: The care provided to patients after gastrectomy was effectively implemented and yielded positive outcomes, contributing to the success of the treatment process.
Keywords: Gastric cancer; postoperative care